Administrative Skills of Student Aides in Camarines Sur Polytechnic Colleges, Philippines - Audal, Rachel Abigail; Binas , Adriana; Oares, Ashley Necole; Marpuri, Jessica C. (The Indonesian Institute of Science and Technology Research, 2025)
The study aims to determine the Administrative Skills of Student Aides in CSPC within the academic year 2024-2025. It determined the profile (age, year level, sex, civil status, and program), administrative skills in records management, communication, technical, and human relations, and factors limiting the proficiency of the respondents. The questionnaire was distributed with widely open access to the respondents and got several ninety-two varied responses from 1st to 4th-year student aides in different programs. The researchers used the descriptive survey method through data gathering instruments such as self-made questionnaires to gather the necessary data. The data gathered were treated statistically through the use of the percentage technique, weighted mean, and Likert-type scale. The major findings are: the administrative skills of student aides are highly competent in human relations while competent in namely records management, communication, and technical. When it comes to the factors limiting the proficiency of the student aides, the underlying indicators on records management, verbal communication, technical, and human relations are perceived as disagreeing while agreeing on the written communication, which means that limits their proficiency. As an output, the recommendation, which is an action plan, is focused on the skills enhancement of the student aides under administrative skills, namely Records Management, Communication, Technical, and Human Relations.